2010
DOI: 10.31729/jnma.89
|View full text |Cite
|
Sign up to set email alerts
|

Need of Improvement in Timing of Prophylactic Antibiotic in Elective Surgery

Abstract: INTRODUCTION: Infections in surgery are major concern of morbidity, mortality, and costs. Timely antibiotic prophylaxis before incision ensures optimum concentration of AP in blood and tissues to prevent surgical site infections . However, proper timing of AP remains problematic as reported by various studies, though none so far from Nepal. Aim of this prospective observational study was to assess and address the issues for improvements in timing of AP. METHODS: The pattern of antibiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…14,15 Hence, antimicrobial prophylaxis should be started prior to contamination, which is considered essential to control bacterial growth and significantly lower the incidence of SSIs. 10,16,17 It is estimated that 60% of SSIs are preventable, mostly related to the use of recommended evidence-based practices such as the timing, selection, and duration of preoperative prophylactic antibiotics. 18,19…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Hence, antimicrobial prophylaxis should be started prior to contamination, which is considered essential to control bacterial growth and significantly lower the incidence of SSIs. 10,16,17 It is estimated that 60% of SSIs are preventable, mostly related to the use of recommended evidence-based practices such as the timing, selection, and duration of preoperative prophylactic antibiotics. 18,19…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that two thirds of SSIs can be prevented [25][26][27] by timely and appropriate administration of AP. 25,[28][29][30] However, compliance with the established guidelines is often far from optimal as found in our earlier study 17 and reported literatures. 14,[18][19][20][21] Awareness, lack of co-ordination and resistance to accept changes are some of the barriers to successful implementation of evidencebased practice of AP.…”
Section: Note: Ap-antibiotic Prophylaxis Discussionmentioning
confidence: 80%
“…In initiation of surgeons, the anesthetist took charge of timing of AP administration with the help of OR nurses. This resulted in 99% (119/120) of AP before incision (from earlier 81% 17 ). Also, the number of patients increased to 48% (from earlier 1% 17 ) who got AP within optimum time of 60 to 30 minutes before incision.…”
Section: Note: Ap-antibiotic Prophylaxis Discussionmentioning
confidence: 99%